1997
DOI: 10.1046/j.1365-2796.1997.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, atherosclerosis and prevalent cardiovascular disease in the elderly: The Rotterdam Study

Abstract: In subjects aged 55-74 years elevated tHcy is associated with an increased risk of atherosclerosis and cardiovascular disease. The lack of association in those aged > or = 75 years most probably reflect selective mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
2
5

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 25 publications
6
44
2
5
Order By: Relevance
“…32 Weak associations, but usually only in certain subpopulations, were found in vascular disease patients and in population-based studies. [15][16][17][33][34][35][36] In our study, we found a borderline statistically significant effect of log tHcy levels on CIMT, so they are still in line with a small effect.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…32 Weak associations, but usually only in certain subpopulations, were found in vascular disease patients and in population-based studies. [15][16][17][33][34][35][36] In our study, we found a borderline statistically significant effect of log tHcy levels on CIMT, so they are still in line with a small effect.…”
Section: Discussionsupporting
confidence: 64%
“…[12][13][14] Atherosclerosis may be another pathway by which tHcy is linked with arterial disease. In general, the evidence of a relationship between tHcy levels and CIMT as a measure of generalized atherosclerosis varies, with some studies reporting this association [15][16][17][18] while others do not. 12,14,[19][20][21] To gain more insight into the association of circulating tHcy with PWV and CIMT, we studied their associations in a population-based sample of 376 men.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 More recently, in the Rotterdam cohort, a positive association between homocysteine and stroke has also been reported. 22 In this study, however, the relation was non-linear with a two-fold increase in risk in the upper quintile relative to rest of the distribution. Additional support for the homocysteine stroke hypothesis is provided by cross-sectional studies, showing independent associations between homocysteine concentrations and carotid atherosclerosis.…”
Section: Recent Prospective Studiescontrasting
confidence: 67%
“…13 There are additional concerns regarding unmeasured and residual confounding due to dietary and other lifestyle factors associated with hyperhomocysteinaemia. 14,15 The findings from the small number of prospective studies that have addressed associations between tHcy concentrations and incident coronary heart diseases (CHD) or stroke are inconsistent [16][17][18][19][20][21][22] Homozygosity for a defective thermolabile variant of MTHFR, a common genetic polymorphism which results in hyperhomocysteinemia, has not been consistently linked with cardiovascular disease endpoints. 23,24 Although the importance of gene markers will vary depending on relevant environmental exposures, diet in this instance, the findings from gene association studies conducted to-date are distinctly unimpressive.…”
Section: Thcy and Cardiovascular Diseasementioning
confidence: 99%
“…Folate intake is associated with homocysteine levels, a well-known risk factor for vascular disease [30][31][32][33][34][35]. It is possible that homocysteine levels contribute to vascular disease through a direct effect on vascular endothelial cells [36].…”
Section: Discussionmentioning
confidence: 99%